2014
DOI: 10.1007/s00210-014-1061-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of masitinib in rats with postischemic stroke

Abstract: This study evaluated the therapeutic potential of masitinib, an oral tyrosine kinase inhibitor with activity against c-Kit and platelet-derived growth factor receptors (PDGFR), to reduce ischemic brain area and neurological deficit. Using a well-established filament model of ischemic stroke in rats, the responses to oral treatment with masitinib alone or in combination with recombinant tissue plasminogen activator (rt-PA) were compared to those after rt-PA (10 mg/kg intravenously (i.v.)) monotherapy. In both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…[13] Therefore, it has long been stressed that there is a connection between the severity of inflammation, the size of the area affected by ischemia and the degree of neurological deficit. [14] In this study, both the increased leukocyte count and the CRP on the first day of the disease were significantly associated with a more severe neurological status in the ultra-acute phase of the disease and with the functional status on the 30th day. Our results are consistent with previous reports and may be supportive of anti-inflammatory strategies in the treatment of stroke.…”
Section: Discussionsupporting
confidence: 47%
“…[13] Therefore, it has long been stressed that there is a connection between the severity of inflammation, the size of the area affected by ischemia and the degree of neurological deficit. [14] In this study, both the increased leukocyte count and the CRP on the first day of the disease were significantly associated with a more severe neurological status in the ultra-acute phase of the disease and with the functional status on the 30th day. Our results are consistent with previous reports and may be supportive of anti-inflammatory strategies in the treatment of stroke.…”
Section: Discussionsupporting
confidence: 47%
“…The role of peripheral monocytes/macrophages remains controversial. There is no clear evidence that they can infiltrate the spinal cord and contribute to MN death [105] unless there is a disruption in the blood-brain barrier [106]. However, their damaging action on peripheral axons has been well recognized [107].…”
Section: Peripheral Immune Systemmentioning
confidence: 99%
“…Accordingly, clinical trials have shown therapeutic effects of masitinib in cases of mastocytosis, a rare disease characterized by abnormal accumulation and activation of mast cells in various tissues and organs (28). Masitinib was also shown to beneficially modulate CNS function in multiple sclerosis (29), stroke (30), and Alzheimer' s disease (31). In addition, a recent phase III clinical trial with masitinib in ALS has shown promising therapeutic effects in a significant group of patients, slowing the deterioration of motor functions and reducing the decline in quality of life (32).…”
Section: Introductionmentioning
confidence: 99%